The Association Between Dietary Inflammatory Potential and Sex Hormones in Male Children and Adolescents Aged 6–19 Years - Qin, Zheng; Liu, Nuozhou; Liao, Ruoxi; Jiang, Luojia; Su, Baihai (Frontiers in Endocrinology, 2021)
Aims: This study aimed to assess the relationship between dietary inflammatory index (DII) and sex hormones in male children and adolescents aged 6-19 years. Methods: We obtained data from the 2013-2016 National Health and Nutrition Examination Survey (NHANES). Male participants aged 6-19 years old with the complete data of DII and sex hormones were included. Weighted multiple regression analysis and subgroup analysis were preformed to estimate the independent relationship between DII and sex hormones. Results: A total of 1717 male participants with the average age of 13.02 ± 3.82 years were enrolled, of whom 41.3% (n=713) were children and 58.47% (n=1004) were adolescents. In children, mean DII was 0.18 ± 1.67, with scores ranging from -4.53 to 4.08. As for adolescents, the mean DII was 0.36 ± 1.98, mean total testosterone (TT) was 376.94 ± 206.69 ng/dl overall. A negative association between DII with TT and estradiol (E2) was observed (TT: β=-11.97, P=0.0006; E2: β=-0.45, P=0.0108) in male adolescent. Subgroup analysis and interaction test results indicated that this association was similar in male adolescents with different body mass index. No statistically significant association was observed in children. Conclusions: Pro-inflammatory diet was associated with lower TT and E2 level in male adolescent, while no association with statistical significance between them was observed in male children. However, more studies are still needed to validate the causal relationship between DII and sex hormones.